2017
DOI: 10.1101/133405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carrion fly-derived DNA metabarcoding is an effective tool for mammal surveys: evidence from a known tropical mammal community

Abstract: Abstract

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 35 publications
2
41
2
Order By: Relevance
“…To conclude, our results suggest that urban fly‐based mammal biodiversity assessment may become a very time‐ and cost‐effective monitoring tool, especially if coupled to the many ongoing urban citizen science initiatives (Silvertown, ). Further investigations of the relative performance of this and other methods would, however, be very welcome, as recent reports have shown that fly‐ and camera trap‐based biodiversity assessments only provide partially overlapping results and can sometimes fail at detecting relatively abundant wildlife species (Lee et al., ; Rodgers et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To conclude, our results suggest that urban fly‐based mammal biodiversity assessment may become a very time‐ and cost‐effective monitoring tool, especially if coupled to the many ongoing urban citizen science initiatives (Silvertown, ). Further investigations of the relative performance of this and other methods would, however, be very welcome, as recent reports have shown that fly‐ and camera trap‐based biodiversity assessments only provide partially overlapping results and can sometimes fail at detecting relatively abundant wildlife species (Lee et al., ; Rodgers et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of invertebrate-derived DNA (iDNA) was put forward as a promising strategy to assess mammalian biodiversity (summarized in: Calvignac-Spencer, Leendertz, Gilbert, & Schubert, 2013;Schnell et al, 2015). Leeches as well as blow and flesh flies (families Calliphoridae and Sarcophagidae; later on flies) were, for example, used as wildlife DNA samplers in pristine tropical areas (Calvignac-Spencer, Merkel, et al, 2013;Lee, Gan, Clements, Wilson, & Adamowicz, 2016;Rodgers et al, 2017;Schnell et al, 2012;Schubert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these risks, it employs different levels of replication (i.e. extraction, PCRs), a curated reference database, and the probabilistic taxonomic assignment method PROTAX (Somervuo, Koskela, Pennanen, Henrik Nilsson, & Ovaskainen, ) that has been shown to be robust even when reference databases are incomplete (Richardson, Bengtsson‐Palme, & Johnson, ; Rodgers et al, ). Leech samples were digested, DNA was extracted, and then mitochondrial target DNA of host species was amplified with PCR and sequenced using Illumina high‐throughput sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Remarkable articles published as Molecular Advances included evaluation of individual barcoding for whole‐genome resequencing (Overgaard‐Therkildsen & Palumbi, ), ancient DNA analyses that identify mollusc shells as historical metagenomic archives (Der Sarkissian et al., ) and development of metabarcoding in carrion flies as a powerful tool for biological surveys of terrestrial mammals (Rodgers et al., ). Additionally, a study by Nazareno, Bemmels, Dick, and Lohmann () provides insight on minimal samples sizes needed for population genomic studies.…”
Section: State Of the Journalmentioning
confidence: 99%